R164H and V240H Replacements by Site-Directed Mutagenesis of TEM-149 Extended-Spectrum β-Lactamase: Kinetic Analysis of TEM-149(H240) and TEM-149(H164-H240) Laboratory Mutants - Perilli, Mariagrazia (American Society for Microbiology, 2013)
Two laboratory mutant forms, TEM-149(H240) and TEM-149(H164-H240), of the TEM-149 extended-spectrum β-lactamase enzyme were constructed by site-directed mutagenesis. TEM-149(H240) and TEM-149(H164-H240) were similar in kinetic behavior, except with respect to benzylpenicillin and ceftazidime. Molecular modeling of the two mutant enzymes demonstrated the role of histidine at position 240 in the reduction of the affinity of the enzyme for ceftazidime.